Structural Analysis of Strigolactone-Related Gene Products - Andersson, Inger; Carlsson, Gunilla H; Hasse, Dirk (Methods in molecular biology (Clifton, N.J.), 2021)
Structural knowledge of biological macromolecules is essential for understanding their function and for modifying that function by engineering. Protein crystallography is a powerful method for elucidating molecular structures of proteins, but it is essential that the investigator has a basic knowledge of good practices and of the major pitfalls in the technique. Here we describe issues specific for the case of structural studies of strigolactone (SL) receptor structure and function, and in particular the difficulties associated with capturing complexes of SL receptors with the SL hormone ligand in the crystal.
Keywords: Protein Binding; Ligand binding; heterocyklické sloučeniny tricyklické; krystalografie rentgenová; ligandy; Structure-Activity Relationship; signální transdukce; Heterocyclic Compounds, 3-Ring; Ligands; Strigolactone; receptory buněčného povrchu; rostlinné proteiny; Signal Transduction; regulace genové exprese u rostlin; molekulární modely; vztahy mezi strukturou a aktivitou; Crystallography, X-Ray; Models, Molecular; vazba proteinů; Strigolactone receptors; Crystallization; Gene Expression Regulation, Plant; konformace proteinů; Lactones; laktony; Receptors, Cell Surface; Macromolecular crystallography; Protein Conformation; Plant Proteins